Health Benefits of Olive Oil and Olive Extracts - Wendy J. Dahl; Michael A. Tandlich; Julie England (EDIS)
Olive oil is known for its health benefits. There are three common types of olive oil, namely virgin olive oil, refined olive oil, and olive pomace oil. Each has its unique processing method, flavor characteristics, composition, and food applications. This 5-page fact sheet describes each of the types of olive oil and their pros and cons. Written by Wendy J. Dahl, Michael A. Tandlich, and Julie England, and published by the Food Science and Human Nutrition Department, June 2016.